Breast cancer: from “maximum tolerable” to “minimum effective” treatment - Veronesi, Umberto; Stafyla, Vaia; Luini, Alberto; Veronesi, Paolo (Frontiers in Oncology, 2012)
Randomized trials have played a fundamental role in identifying better treatments for most type of diseases, especially in the oncological field. In breast cancer the shift from "maximum tolerable" to "minimum effective "treatment has been evident since the 70s and has been based on the results of international randomized trials. The progress of breast surgery represents an excellent model of the evolution of science and the aim of this article is to review the main randomized studies that changed everyday practice in breast surgery.